THE COMPULSORY, FREE UNIVERSAL BASIC EDUCATION ACT 2004 AND THE REALITY OF OUT OF SCHOOL CHILDREN IN NIGERIA - Popoola, Bolaji Gabriel (African Journal of Educational Management, 2021)
Globally, the growing population of out-of-school children has become a major concern to education stakeholders. It is more of concern in Nigeria, as the available data suggests it has the highest population of the out-of-school children in the world. This concern has generated debates globally as regards what should be done to mitigate this problem. The enacting of Compulsory, Free Universal Basic Education Act (CFUBEA) 2004 was designed to make basic education accessible to all children. Years after its enactment, the issue of out-of-school children is still trending with the population growing. A review of Nigeria law reports was made to see if there had been prosecution of violators of CFUBEA 2004 between 2008-2018, however, no case related was found. This gave an expose on the extent to which the punitive clause of CFUBEA 2004 have been enforced. It was recommended that the government should ensure the enforcement of the CFUBEA 2004.